2018
DOI: 10.1002/bdr2.1400
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based surveillance of congenital heart defects among adolescents and adults: surveillance methodology

Abstract: Background: Improved treatment of congenital heart defects (CHDs) has increased survival of persons with CHDs; however, no U.S. population-based systems exist to assess prevalence, healthcare utilization, or longer-term outcomes among adolescents and adults with CHDs. Methods: Novel approaches identified individuals aged 11–64 years who received healthcare with ICD-9-CM codes for CHDs at three sites: Emory University in Atlanta, Georgia (EU), Massachusetts Department of Public Health (MA), New York State Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…The pilot study identified a total of 14 183 CHD patients who met the case definition. Glidewell et al explain the methodology of the pilot study . CHD codes were categorized into five groups similar to Marelli et al which integrates both severity and anatomy: severe, shunts, shunts plus valve, valve, and other CHD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pilot study identified a total of 14 183 CHD patients who met the case definition. Glidewell et al explain the methodology of the pilot study . CHD codes were categorized into five groups similar to Marelli et al which integrates both severity and anatomy: severe, shunts, shunts plus valve, valve, and other CHD.…”
Section: Methodsmentioning
confidence: 99%
“…CHD codes were categorized into five groups similar to Marelli et al which integrates both severity and anatomy: severe, shunts, shunts plus valve, valve, and other CHD. The modified Marelli classification accounts for ICD‐9‐CM codes and simplifies this classification to severe and not severe as described by Glidewell et al Severe CHD was defined as a CHD usually requiring surgical or catheter intervention within the first year of life. The remaining codes were combined and classified as “not severe” for pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…To identify hospital readmissions, information from the STS database was linked to Emory University's population-based surveillance data repository for individuals with a CHD diagnosis that includes data from 2011-2013. The data are part of an expanded collaboration between Emory University and the Centers for Disease Control and Prevention 16 that includes Georgia Medicaid administrative claims, allowing for the follow-up of patient outcomes longitudinally across multiple sites in Georgia 16,17 .…”
Section: Data Sourcementioning
confidence: 99%
“…Insurance payer status was categorised as public (including Medicare and Medicaid), private/employer-based, uninsured or self-pay, or other/unknown. Severity of CHD disease was classified as severe or not severe using a modified Marelli classification scheme, as outlined in Glidewell et al 16,18 . Co-morbidities of interest were identified using ICD-9-CM codes and were classified as cardiac, pulmonary, pulmonary hypertension, renal, hepatic, neurologic, haematologic, genetic syndrome, nutritional (specifically, overweight/obesity, underweight, or failure to thrive), or endocrine disease.…”
Section: Patient and Admission Characteristicsmentioning
confidence: 99%
“…The eight HSAs for New York are Western NY, Finger Lakes, Central NY, NY-Penn, Northeastern NY, Mid-Hudson, New York City (NYC), and Nassau-Suffolk. Eligible CHD ICD-9-CM diagnosis codes for each person were categorized into five hierarchical, mutually exclusive severity groups (from top to bottom of hierarchy: severe, shunt + valve, shunt, valve, and other) considering anatomy and hemodynamic severity (8). A dichotomous severe (severe only) and non-severe (shunt + valve, shunt, valve, and other) CHD categorization scheme was also employed for select analyses.…”
Section: Study Population and Data Sources The Legislatively Mandatementioning
confidence: 99%